Depth of invasion alone as an indication for postoperative radiotherapy in small oral squamous cell carcinomas: An International Collaborative Study - Ebrahimi, Ardalan; Gil, Ziv; Amit, Moran; Yen, Tzu‐Chen; Liao, Chun‐ta; Chaturvedi, Pankaj; Agarwal, Jai Prakash; Kowalski, Luiz P.; Köhler, Hugo F.; Kreppel, Matthias; Cernea, Claudio R.; Brandao, Jason; et al. (Head & neck, 2019)
Background We aimed to investigate whether depth of invasion (DOI) should be an independent indication for postoperative radiotherapy (PORT) in small oral squamous cell carcinomas (SCC). Methods Retrospective analysis of DOI (<5, 5 to <10, ≥10 mm) and disease‐specific survival (DSS) in a multi‐institutional international cohort of 1409 patients with oral SCC ≤4 cm in size treated between 1990‐2011. Results In patients without other adverse factors (nodal metastases; close [<5 mm] or involved margins), there was no association between DOI and DSS, with an excellent prognosis irrespective of depth. In the absence of PORT, the 5‐year disease‐specific mortality was 10% with DOI ≥10 mm, 8% with DOI 5‐10 mm, and 6% with DOI <5 mm (P = .169), yielding an absolute risk difference of only 4%. Conclusion The deterioration in prognosis with increasing DOI largely reflects an association with other adverse features. In the absence of these, depth alone should not be an indication for PORT outside a clinical trial.